Youth Elbow Throwing Injuries: Current Concept Review - Dove, James; Painter, David; Testa, Edward; Schiller, Jonathan; Kriz, Peter; Cruz, Aristides (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Youth elbow throwing injuries have been increasing among the pediatric population as more children participate in overhead sports, compete at high levels, and specialize in a single sport at an earlier age. The majority of these elbow injuries are attributable to overuse. In order to decrease the incidence of elbow injuries, recommendations and guidelines have been established and adopted by the Little League Baseball organization and other youth baseball organizations in America. There has been some success with these guidelines as they have been shown to decrease the risk of developing injury. Despite having guidelines, however, adolescents who compete in overhead sports remain at high risk of developing overuse injury, and the spectrum of injury is commonly seen in pediatric orthopedic offices. In this review, we describe six different elbow injuries associated with overuse and their specific management and treatment strategies: medial epicondyle apophysitis, medial epicondyle fracture, capitellar osteochondritis dissecans, Panner’s disease, UCL sprain, and olecranon stress injury. The purpose of this review is to highlight the spectrum of overuse elbow injuries seen in the pediatric population and briefly summarize the management of each injury.